The quantum society : mind, physics and a new social vision - Zohar, Danah (Flamingo, 1993)
This work goes to the heart of contemporary moral and political dilemmas arising from the challenges of pluralism and rapid change, the inability of traditional society to cope with these, and the need to get beyond the stale conflict between selfish individualism and stifling collectivism. Drawing on the many uncanny analogies between quantum reality and the dynamics of self and society, Zohar and Marshall argue that we can change our social perceptions, values and behaviour by drawing our deepest images and metaphors from the nature of the mind and the wider nature of the physical universe itself. They offer a new theory of cosmic and social evolution that allows us to rediscover the meaning and purpose of society: a radically new vision of how we might, through dialogue, arrive at a new consensus that is itself a rich celebration of diversity. "The Quantum Society" builds on and extends the insights of Danah Zohar's book "The Quantum Self".